Health care experiences of individuals accessing or undergoing in vitro fertilization (IVF) in the U.S.: a narrative review of qualitative studies - Peterson, Summer K.; Jennings Mayo-Wilson, Larissa; Spigel, Lauren; Morgan, Isabel; Parker, Adriana (Frontiers in Reproductive Health, 2025)
BackgroundIn vitro fertilization (IVF) is an increasingly common method of assisted reproduction given the high rates of infertility in the United States (U.S.). However, despite growing utilization of IVF technologies, there is little known about the experiences of those accessing or undergoing IVF, particularly among adults in the U.S. The aims of this review are to (1) explore how economic, emotional and physical health, and interpersonal relationships impact and are impacted by accessing or undergoing IVF, and (2) understand the role of healthcare providers and the healthcare system.MethodsA narrative review was conducted to summarize the current literature and provide insight into potential channels for care improvement. Eligible studies were published in English from 2013 to 2024 which qualitatively evaluated experiences of individuals and couples accessing or undergoing IVF. Peer-reviewed publications were identified from three electronic bibliographic databases. Methodologic rigor was assessed by two reviewers who also abstracted data on the study's characteristics as they pertained to four domains: health systems, economic, interpersonal, and physical and emotional health. Among the 32 papers retrieved for review, 22 met inclusion criteria and were retained for analysis.ResultsThe available literature suggests accessing and undergoing IVF can be positively and negatively influenced by health systems, economic, interpersonal, and physical and emotional health factors. Often an individual or couple experiences multiple factors that compound to create a complex situation. Health systems-related factors included physician interaction and challenges with information volume and processing. Economic challenges primarily pertained to financing IVF and navigating insurance coverage. Interpersonal factors related to changes in relationships with partners, family members, and friends due to IVF. Physical health concerns (e.g., pain) and emotional health concerns (e.g., sadness, stress) were also noted by all included papers.ConclusionsEfforts to improve care experiences of adults accessing or undergoing IVF are urgently needed. The evidence base points to a need for provider sensitivity trainings, clinic-based intervention, and community education in both physical and virtual spaces.